2019
DOI: 10.1007/s10658-019-01869-x
|View full text |Cite
|
Sign up to set email alerts
|

The ENHANCED MAGNAPORTHE RESISTANCE 1 locus affects Ramularia leaf spot development in barley

Abstract: Ramularia leaf spot (RLS) is a newlyimportant disease of barley which is caused when the fungus Ramularia collo-cygni enters necrotrophic development during colonisation of the host. Mutant alleles at the barley MILDEW LOCUS O, mlo, locus confer broad spectrum durable resistance against the powdery mildew fungus, Blumeria graminis f. sp. hordei, but can enhance susceptibility to pathogens with necrotrophic development stages such as R. collo-cygni. Given the importance of mlo in spring barley breeding programm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…To date, no source of genetic resistance has been identified in barley; however, the genetic background of the host is known to play a role in disease development as varieties carrying the mildew locus O ( mlo ) mutation, which confers resistance to powdery mildew, exhibit increased susceptibility to RLS [ 13 ]. Further supporting the role of the host genetic background in RLS development, a loss of function mutation of the Enhanced Magnaporthe 1 ( emr1 ) gene in a mlo background mitigates the effect of the mlo mutation on RLS severity leading to decreased RLS symptoms [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, no source of genetic resistance has been identified in barley; however, the genetic background of the host is known to play a role in disease development as varieties carrying the mildew locus O ( mlo ) mutation, which confers resistance to powdery mildew, exhibit increased susceptibility to RLS [ 13 ]. Further supporting the role of the host genetic background in RLS development, a loss of function mutation of the Enhanced Magnaporthe 1 ( emr1 ) gene in a mlo background mitigates the effect of the mlo mutation on RLS severity leading to decreased RLS symptoms [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…mildew resistance locus 0 (MLO) genes are used in breeding new varieties for powdery mildew resistance but these genes have no effect on R. collo-cygni in grain (Hofer et al, 2015). Another study by McGrann et al (2020) concluded that the Enhanced Magnaporthe Resistance locus (EMR1) reduce RLS development. Additionally, only a few data of quantity of sporulation between different varieties (Hoheneder et al, 2021) or different culture parameters like light or nutrients are available.…”
Section: Introductionmentioning
confidence: 99%